ORGANIC APPROACH FOR POPULARIZATION OF SUSTAINABLE AQUACULTURE - BHAUMIK, UTPAL; NATH, D.; GUPTA, A.; SETT, P.; SAHA, SUMAN; CHATTERJEE, J. G. (Journal of the Inland Fisheries Society of India, 2022)
Organic farming has gained popularity all over the world as sustainable farming system, which maintains the long-term fertility of the soil and uses less of the Earth’s finite resources to produce quality, nutritious food. Organic farming is based on a holistic view where nature is considered as a whole with an intrinsic value of its own. On the environmental front, especially the pollution resulting in from nitrogen and pesticide use is of increasing concern. Organic farming also offers biodiversity benefits for the soil and aquatic ecosystems. People are to take moral responsibility regarding the ecological, economical and social aspects of aquaculture production. Broad general principles such as good nutrition, the maintenance of fish health and recycling of nutrients where possible are relevant to fin fish and shell fish production (Thomas, 1994; Laired, 1999). Basically, the urgent task facing Indian aquaculture today is reduction in the cost of fish production in sustainable manner and putting the available resources to optimum use through new practices/technologies. With a view to popularizing organic farming for sustainable aquaculture in the rural areasdemonstrations in some areas of West Bengal were carried out utilizing organic manures namely vermi-compost, cow dung, compost and duck droppings. The abiotic and biotic factors were observed to be conducive for favourable fish production. The productions obtained under carp culture utilizing duck droppings, raw cow dung, compost, vermicompost were 3216 kg/ha/yr, 2486 kg/ha/yr, 2280 kg/ha/yr, 1808 kg/ha/yr respectively. Low cost involved in the experimentations has been motivating the fish farmers towards the adoption process.Key words: Organic, aqua-farming, environment, sustainable, popularization.